Moldify business plan - Benedicto, Stephanie Francisco (Animo Repository, 2022)
Moldify is a start-up venture owned by five (5) general partners namely Stephanie Benedicto, Alliya De Guzman, Christine Fabella, Danilyn Severa, and Sophia Topacio. In Moldify, our vision is to be the top seller of artisan kits and we intend to provide maximum ease and convenience when creating our mission is to provide high quality and affordable all-in-one kits. Our brand aims to spark the compassion, creativity and comfort of our customers by bringing satisfaction through our product and service. We want to achieve financial stability and look into expansion that will soon allow us to create market shares and be a subject of investment in the future.